2018
DOI: 10.1128/jvi.02106-17
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Conformational Changes in the Capsid of Human Papillomaviruses Contribute to Asynchronous Uptake into Host Cells

Abstract: The human papillomavirus type 16 (HPV16) is the leading cause of cervical cancer. For initial infection, HPV16 utilizes a novel endocytic pathway for host cell entry. Unique amongst viruses, uptake occurs asynchronously over a protracted period of time with half-times between 9-12 h. To trigger endocytic uptake, the virus particles need to undergo a series of structural modifications after initial binding to heparan sulfate proteoglycans (HSPG). These changes involve proteolytic cleavage of the major capsid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 98 publications
2
50
0
Order By: Relevance
“…Recent studies have shown the importance of KLK8 during viral infections, such as those produced by the human papillomavirus (HPV). It has been proposed that KLK8 is involved in the entry of the virus into the cells through the proteolytic cleavage of L1 protein, the main capsid protein of HPV (Cerqueira et al, 2015;Becker et al, 2018). Remarkably, viral agents like HPV are believed to participate in the pathogenesis of multiple sclerosis where viral components act as a short-term risk factor for multiple sclerosis onset or relapse in the established disease.…”
Section: Klks Associated To Viral Infections That Can Affect the Cnsmentioning
confidence: 99%
“…Recent studies have shown the importance of KLK8 during viral infections, such as those produced by the human papillomavirus (HPV). It has been proposed that KLK8 is involved in the entry of the virus into the cells through the proteolytic cleavage of L1 protein, the main capsid protein of HPV (Cerqueira et al, 2015;Becker et al, 2018). Remarkably, viral agents like HPV are believed to participate in the pathogenesis of multiple sclerosis where viral components act as a short-term risk factor for multiple sclerosis onset or relapse in the established disease.…”
Section: Klks Associated To Viral Infections That Can Affect the Cnsmentioning
confidence: 99%
“…Given that furin-processing at the cell surface is requisite for successful infection and partially dictates the asynchronous uptake of HPV virions ( 39 , 40 ), we sought to assess whether RTD-1 would still be able to inhibit fpc HPV16 PsV. We found that fpcPsV are just as sensitive to RTD-1 inhibition as regular PsV ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies employing co-immunoprecipitation and flow cytometry indicate that HPV binds directly to integrin α6 [11][12][13] . On the other hand, it is also assumed that the HPV capsid protein binds to a set of primary receptors different from integrin α6 16,39 , undergoes conformational changes and is then transferred to a secondary receptor complex 34,[48][49][50] which could be part of a TEM. Our experiments do not allow to differentiate between these binding states which may coexist in the same cell membrane.…”
Section: Scientific Reports |mentioning
confidence: 99%